Design and control of a virtual synchronous generator-based microgrid - Lim, Joel Bing Heng (Nanyang Technological University, 2021)
In today’s fast advancing technological world, the use of renewable energy has become increasingly popular due to its benefits that it would bring towards our mother Earth. This paper will explore the methods in the design of a virtual synchronous generator (VSG) – based microgrid system which can mimic the characteristics and properties of conventional synchronous generators. The VSG design will be implemented in the PLECS software. The VSG will consist of two control loops, the inner loop voltage and current control which can provide the appropriate voltage regulations and system stability and the outer loop frequency and power control, which provides frequency support and virtual inertia emulation. The simulation of a 1kW 3-phase power system with an increase in 30% load change will be ran in order to determine the effectiveness of the system.